Youth insight and preferences in religious and spiritual tourism - Ali, Nur Hidayah; Md Sawari, Siti Salwa; Abu Hasan, Nurul Nadirah; Gokce, Akif (KSTCL Press, 2024)
Purpose: This study investigates the knowledge and needs of Malaysian youth regarding religious and spiritual tourism.